Wybrane miary efektywności systemów bonus-malus ubezpieczeń komunikacyjnych OC - Szymańska, Anna (Chosen Efficiency Measures of Bonus-Malus System of Civil Responsibility Car Insurance, 2008)
In civil responsibility car insurance the individual premium is estimated in two stages. The first stage is the estimation of the basic premium on the basis of prior factors - known risk factors such as driver's sex and age, type of car etc. The second stage is the posterior tarrification i.e. determining the individual premium on the basis of the damage history of the insured. This stage is called the bonus-malus system. The paper presents some selected methods of the assessment of the effectiveness of the bonus-malus system. The effectiveness of the bonus-malus system of an insurance company from Łódź was also investigated on real data.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 428-435